Vitamin D and its Role in Cell Cycle Dynamics: A Review of the Molecular and Clinical Studies - Sastradinata, Irawan; Murti, Krisna; Saleh, Irsan; Nurseta, Tatit (Newinera Publisher, 2025)
Vitamin D is an essential nutrient that not only plays a role in calcium homeostasis and bone health, but also has broad functions in the regulation of various biological processes, including cell cycle dynamics. This study aims to examine in depth the role of vitamin D in cell cycle dynamics based on evidence from molecular and clinical studies. The method used was qualitative research with a literature study approach, where data was collected from relevant articles such as PubMed, EuropePMC, and Google Scholar. Analysis was carried out through the process of filtering, presenting data, and drawing conclusions. The results showed that vitamin D in its active form, 1,25-dihydroxyvitamin D3, interacts with the vitamin D receptor (VDR) in cells and modulates the expression of genes involved in cell proliferation. This mechanism involves an increase in the expression of cell cycle inhibitory genes, such as p21 and p27, and a decrease in the expression of cell cycle promoting genes, such as cyclin D1, which contributes to the arrest effect on the cell cycle. Thus, in addition to being important for bone health, vitamin D has a significant role in cell cycle regulation, and its deficiency can increase the risk of various diseases, including cancer. Therefore, maintaining optimal vitamin D levels through sun exposure, consumption of foods rich in vitamin D, or supplementation is essential. Further research is needed to understand the role of vitamin D in genetic regulation, particularly in relation to cancer.